Emotional Intelligence, Socio - Emotional Competence and Human Capital - Choudhury, Dr. Jyotirmayee (RA Journal of Applied Research, 2021)
The concept of emotional intelligence and emotional competency is contemporary issue in the management literature. Therefore, it has become imperative to study, understand and leverage it for the sake of enhancing the capacity of human capital at the level of individual as well as organizations. As the pace of change is fast and uncertain in the world of work, it is making more and more demands on a person’s cognitive, emotional and physical resources. These set of capabilities are becoming progressively significant. It is because majority of the concerns in organization involve people in different roles. Hence, emotional intelligence must become a determining factor for their effective management. Emotional and personal competencies are inevitable to identify measure, predict and manage performance at workplace resulting in its effectiveness. Thereby, it boosts the worth of the human capital. That is the reason why, the competencies possessed by the people have a significant bearing on the extent to which they can actualize their emotional intelligence. The current paper sets out to examine the concept and correlation between the emotional intelligence, socio emotional competencies, emotionally intelligent behavior and human capital. The study recommends that emotional intelligence is significantly related with the socio-emotional competencies which ultimately strengthen emotionally intelligent behavior to leverage human capital at individual and organizational level.